Natural products and Chagas’ disease: the action of triterpenes acids isolated from Miconia species - Ferreira, Daniele da Silva; Universidade de Franca (2013)
The protozoan Trypanosoma cruzi causes Chagas’ disease, a neglected illness that remains a relevant public health concern in Latin America. In Brazil, Benznidazole is available for its treatment. This compound is effective against circulating forms of the parasite in the acute phase of the disease, but its efficacy during the chronic stage is debatable. The search for new medications that can treat Chagas’ disease is therefore mandatory. Natural sources display a wide range of secondary metabolites and may play an important role in the discovery of new potential drugs. Miconia is one of the largest genus of the family Melastomataceae and includes approximately 1,000 plant species; Brazil alone is home to approximately 250 of these species, which exist in forests and savannas. Studies on the various biological activities of the Miconia species have reported promising results. Several researchers have screened these plants as well as their extracts in vitro against trypomastigote forms of T. cruzi, which displayed significant trypanocidal activity. It has been demonstrated that the presence of ursolic and oleanolic determines this biological activity.